2016
DOI: 10.1186/s40494-016-0087-0
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic arsenic sulfides in Japanese prints of the Meiji period

Abstract: A multi-analytical investigation of Japanese woodblock prints ranging in date from 1864 to 1895 and covering essentially the time span between the very end of the Edo period and the middle of the Meiji period showed a widespread use of arsenic sulfides for yellow and green colored areas (the latter obtained by mixing Prussian blue to the yellow arsenic sulfides). Analysis by optical microscopy, X-ray fluorescence spectroscopy, Raman microscopy, and Scanning Electron Microscopy confirmed that the yellow pigment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
12
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 13 publications
4
12
1
Order By: Relevance
“…The peak centered at 471 cm −1 is characteristic of free sulfur. The artificial orpiment spectra agreed well with previously published work [8,17].…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…The peak centered at 471 cm −1 is characteristic of free sulfur. The artificial orpiment spectra agreed well with previously published work [8,17].…”
Section: Resultssupporting
confidence: 82%
“…On average, the arsenic and sulfur-containing particles had an arsenic content of 47.5 ± 4.0 wt% and a sulfur content of 52.6 ± 4.0 wt%. The measured arsenic and sulfur content, and in particular, the excess amount of sulfur is strongly indicative of artificial arsenic sulfide [17,18]. Trace amounts of copper were also detected in the particles shown, and no As 2 O 3 was detected on the paper fibers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While wear in the keyblock can give important indications on the relative chronology of production of individual impressions of the same print, pigment use is a valuable source of information towards dating and authenticating artifacts [4][5][6][7]. This approach has previously been applied to Japanese woodblock prints, using pigments such as synthetic ultramarine blue or orpiment as well as organic colorants as dating markers [3,[8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…1 PB is also a chronological marker since it was introduced in the Japanese woodblock printing process at the end of the 1820s. Few analytical studies were conducted on such artworks [2][3][4][5][6][7][8][9] but the common use of indigo and PB in Japanese paintings, alone or mixed together, has been observed. [10][11][12] The majority of the studies conducted on 19th century ukiyo-e have also identified or have traced the presence of PB in blue colors as the primary or as in mixtures to obtain different shades of blue, green, and violet.…”
Section: Introductionmentioning
confidence: 99%